Beyond Rankings: UI GreenMetric Network Online Courses on Sustainability - Junaidi, Junaidi; Sari, Riri Fitri; Ramadianti, Sabrina Hikmah; Sidiyanto, Yogi Andrian (Universitas Diponegoro, 2023)
UI GreenMetric World University Rankings is the first sustainability ranking recognizing universities that prioritize sustainability in their programs. It extends into a network of universities conducting global activities for knowledge sharing. To further its goal of creating global sustainability leaders, UI GreenMetric offers an online course on sustainability since 2020. Managed by international and Indonesian groups, the course focuses on international student collaboration to learn about intricate relationships between the economy, social life, and the environment, and the effects of human activities on the planet with solutions to address them. The UI GreenMetric Online Course on Sustainability utilizes synchronous and asynchronous learning systems and enables students to develop project proposals related to SDGs. The course evaluation indicates a high level of student engagement and utilization of the Moodle platform. The assessment instruments, including quizzes, question forums, and project reports, received positive feedback and were effective in supporting student learning. Collaborative group work and exposure to multicultural perspectives enriched the learning experience. While the adequacy of weekly materials was generally acknowledged, some participants suggested areas for improvement. Lessons learned from the course include acquiring SDGs knowledge, the diverse perspectives gained from professors and students, and establishing international networks. The findings underscore the significance of collaboration and identify opportunities for further enhancement in future iterations of the course.